Feasibility and safety of 0.018-inch guidewire-supported distal access catheters in establishing transradial neurointerventional access - Li Bao; Yawen Zhao; Junhui Li; Shuang He (Scientific Reports)
Abstract Transradial access (TRA) in neurointervention has gained popularity due to fewer procedural complications and reduced recovery time compared to transfemoral access (TFA). This study aimed to assess the feasibility and safety of using 0.018-inch guidewire (018’’GW)-supported distal access catheters (DAC) in establishing transradial neurointerventional access, in comparison to the Ballast long sheath. We performed a retrospective review of a prospective database of transradial neurointervention with Ballast long sheath-supported DACs or 018’’GW-supported DACs. Patient demographics, baseline clinical characteristics, and detailed procedural information were recorded. The success rate of TRA neurointervention using 018’’GW-supported DACs was comparable to that of the Ballast long sheath protocol (100% vs. 96.3%, p = 0.19). Both protocols achieved comparable placement heights of DACs and outcomes for aneurysm and symptomatic intracranial atherosclerotic stenosis (sICAS) treatment. Moreover, the 018’’GW-supported DACs significantly decreased 6-month radial artery occlusion (RAO) rates (5.88% vs. 18.18%, p = 0.045) without any major vascular or neurological complications. This study highlights the feasibility and safety of 018’’GW-supported DACs in TRA neurointervention, offering a viable alternative with reduced complications and enhanced distal stability in comparison with the Ballast long sheath.